RESPON FISIOLOGI TERHADAP CEKAMAN KEKERINGAN DENGAN INDUKSI PAKLOBUTRAZOL DAN INTERVAL PENYIRAMAN PADA KEDELAI (Glycine max (L.) Merrill) - Rita Ningsih; HARDIANTY FAIZAL (Bioscientiae, 2024)
This research aims to observe the combination effect of watering interval, and paclobutrazol toward chlorophyll, alkaloid and anthocyanin content of soybean leaves (Glycine max (L.) Merrill) growing in ultisol soil. This experimental research used a factorial complete randomized design with three replicates. There were two factors: watering interval (H1: every day, H2: 2 days and H3: 3 days) and paclobutrazol concentrations (P0: 0 ppm, P1:100 ppm, and P2: 200 ppm). The data analysed by two way Anova (Analysis of Variance) and continued with Tukey test. The result showed that watering interval and paclobutrazol had significantly interaction effect on chlorophyll, alkaloid and anthocyanin. Treatment combination which gives the highest content of chlorophyll was H2P2 (33.2 CCI), alkaloid was H3P2 (0.0177 g), and also anthocyanin was H3P2 (0.721%). It can be concluded that the application of paclobutrazol can stimulate physiological responses in the form of increasing the content of chlorophyll, anthocyanins and alkaloids so that the survival capacity of soybeans increases under drought stress conditions.